0D/2D heterojunction constructed by high-dispersity Mo-doped Ni2P nanodots supported on g-C3N4 nanosheets towards enhanced photocatalytic H2 evolution activity. (3rd September 2020) - Li, Chunmei; Wu, Huihui; Hong, Shihuan; Wang, Yun; Song, Ning; Han, Zhonghui; Dong, Hongjun
Abstract: Development of low cost and efficient non-noble-metal cocatalyst is still a hot topic to improve the activity of g-C3 N4 in photocatalytic water splitting to produce H2 . As a potential cocatalyst in photocatalytic application, transition metal phosphides (TMPs) have been proved to greatly enhance the photocatalytic H2 evolution performance comparable to noble metal Pt. Modifying TMPs by incorporation of hetero-metal has also been reported as an effective strategy for their electronic structure regulation and optimizing the intermediates absorption energy, however, which is rarely reported in the field of photocatalysis. Herein, the 0D/2D heterojunction is constructed by high-dispersity Mo-doped Ni2 P nanodots supported on g-C3 N4 nanosheets, which exhibits the significantly improved photocatalytic H2 evolution performance compared with that of Ni2 P/g-C3 N4 and Pt/g-C3 N4 . Specifically, the optimal H2 evolution rate reaches 67.6 μmol h −1 over Mo–Ni2 P/g-C3 N4 sample, which is 6.0 and 2.4 times higher than those of Pt/g-C3 N4 and Ni2 P/g-C3 N4, respectively. The fascinating result mainly stems from the improved separation efficiency of charge carriers and more effective electron donating reaction sites resulted from the electronic structure adjustment through doping Mo element into Ni2 P as cocatalyst. This work provides a valid evidence for the modification of cocatalyst to realize high H2 evolution performance, opening up new opportunities and possibilities for the application of TMPs in the photocatalytic field. Graphical abstract: High-dispersion 0D Mo-doped Ni2 P nanodots are attached on the 2D g-C3 N4 nanosheet surface to form 0D/2D heterojunction, which exhibits the significantly enhanced photocatalytic H2 evolution performance compared with Ni2 P/g-C3 N4 and Pt/g-C3 N4 under the same experimental conditions. Image 1 Highlights: 0D/2D Mo–Ni2 P/g-C3 N4 heterojunction is constructed successfully. Mo introduction into Ni2 P offers more effective electron donating reaction sites. This heterojunction exhibits higher photocatalytic H2 evolution performance. This work provides a valid evidence for cocatalyst modification.